If the universe is teeming with aliens ... WHERE IS EVERYBODY? : seventy-five solutions to the Fermi paradox and the problem of extraterrestrial life /: seventy-five solutions to the Fermi paradox and the problem of extraterrestrial life. (2015) - Webb, Stephen
No abstract available